Ecological distribution and anatomical development of Dioscorea Alata L. and D.Esculenta (LOUR.) Burkill in Kelantan and Terengganu, Malaysia - Nor Azahana Abdullah
A total of 52 accessions of Dioscorea alata L. and 23 of D. esculenta (Lour). Burkill were collected in the states of Terengganu and Kelantan. The morfological features of both species were characterized. Accession of D. alata was evaluated anatomically at different stages of growth using histological technique and scanning electron microscope. Morphological variations were demonstrated in the accession of D. alata and D. esculenta in the leaf and tuber characteristics. Tip of leaf apical meristem, dome shape and later knob formed at the base. The knob extended to develop into the leaf primordium. Leaf initiation showed a decussate arrangement. The leaf upper epidermis was thicker than the lower one. The palisade tissue started as a dense tissue without any clear shape but later became elongated. The spongy layer in the early stage was without any clear shape and contained many cells which were stained red, indicating the presence of tannin. These stages require much protection which was given by the presence of the chemical. Further protection was given by the glands and raphides. The midrib, the xylem tissue was located at the upper part and the phloem at the lower region. The development of the leaf can be followed easily by the formation of xylem vessel, its number and thickness of the secondary wall. Early structural changes in the stem ocured below the shoot apical meristem where the epidermis, ground tissue and protoxylem were observed. Further changes were the formation of radial division from the centre of the stem towards the cortex. Within these radial divisions, the number and size of xylem vessels increased. A closer look among the xylem vessels showed the presence of phloems with the identification of sieve plates. Pith was present like the eudicots. Sclerenchyma tissue formed between the cortex and the inner ground tissue. The vascular tissue appeared as few small pore formations in the root and developed into many larger pores radially without formation of pith. The phloems formed alternately with the xylem as in monocots. The stele is narrow compared to the cortex which was very large. Histological changes took place at the base of the stem and the ground tissues initiate the bulging of the tuber. The presence of cork cells were found at an early stage and in old tuber layer of sclerenchyma developed. The stages of growth of D. alata can be associated with changes in structural features which can be used as markers and in further biochemical study can result in formation which can be used in the regulation of growth and development in the species.